USABILITY OF THE GOOGLE EARTH ENGINE (GEE) TOOL FOR MONITORING AND COMBATING DEFORESTATION IN THE AMAZON REGION (REMUNOM, 2025)
The Amazon region represents an environmental heritage of global significance, whose integrity has been increasingly threatened by illegal deforestation and the improper use of land. In this context, the use of remote sensing technologies has proven essential in addressing these challenges. This article analyzes the usability of the Google Earth Engine (GEE) tool as a strategic instrument for monitoring and combating deforestation in the Amazon. The research adopted a methodology based on a literature review, using databases such as Scopus, SciELO, CAPES, and Web of Science. Selection criteria prioritized studies published between 2017 and 2023 that focused on the use of GEE in forest areas. The results show that GEE stands out for its user-friendly interface, high cloud processing capacity, and extensive satellite data repository, including Landsat, MODIS, and Sentinel, enabling near real-time analysis. The tool has been successfully applied in land use and land cover mapping, identification of critical areas, and decision-making support for public agencies, NGOs, and researchers. Furthermore, it presents low operational costs and can be used even by users with limited technical knowledge. The analysis reinforces the role of GEE as a facilitator of evidence-based environmental management, promoting transparency and efficiency in enforcement and territorial planning actions. It is concluded that GEE is a promising tool for the preservation of the Amazon rainforest, contributing to the reduction of deforestation and the strengthening of environmental public policies.